A vizinhança fantasma: um panorama da coralidade no cinema e outras artes - Rodrigo Hubert Leme (2022)
This paper seeks to understand the apparition of chorality in Cinema, especially in contemporary Brazilian Cinema. Starting from a theoretical background on studies about chorality in research fields of theater, sound, literature, and correlated areas, followed by an analysis of the history of the term within the cinematographic field itself, there is an examination of the multiple forms of expression of chorality in current Brazilian cinema. Thus, the thesis makes a proposition about an understanding of chorality in a broad sense, seeking to initiate possible discussions and analysis on the subject. Finally, the text proposes a comparative analysis between Long Way Home (2019, André Novais) and The Hidden Tiger (2013, Affonso Uchoa), with the understanding that these films end up bringing together authors, crew, actors, and spectators under the logic of a chorality, established as neighborhood.